Payoffs for California College Students and Taxpayers from Investing in Student Mental Health - Ashwood, J. Scott (RAND Corporation, 2015)
Reports results of a survey to assess the impact of CalMHSA's investments in mental health programs at California public colleges and estimates the return on investment in terms of student use of treatment, graduation rates, and lifetime earnings.